Penerapan Metode Simple Additive Weighting (SAW) pada Sistem Pendukung Keputusan Pemilihan Lokasi untuk Cabang Baru Toko Pakan UD. Indo Multi Fish - Resti, Nalsa Cintya (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2017)
There are several ways used by a company / store to grow its business. One that can be done is to open a new branch elsewhere. Selection of areas that will be made a new branch also can not be chosen arbitrarily. There are criteria that can increase the company's profit, in this case UD Indo Multi Fish. Using the Simple Additive Weighting method (SAW) can provide recommendations on which areas are appropriate to be used as the new branch of the store. The highest ranking value is an area that can be recommended to open a new branch.